Strategy and Whole Course Implementation Schemes of Smart Energy - Jia TAO; Tengbo DING; Kanghong NING; Nong ZHANG (发电技术)
After guideline[2016]392 was issued by the government, smart energy has become a hot pursuit within power system, manufacturers and social capital, while little connotation of which has been known. Understanding of smart energy is often focused on construction of energy infrastructure, distributed power, energy storage, distribution network, which do not belong to consumers. Basic social appeal, strategic framework and systematic implementation plan of smart energy were discussed.